2015
DOI: 10.1124/mol.114.095265
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of [3H]VUF11211, a Novel Radiolabeled Small-Molecule Inverse Agonist for the Chemokine Receptor CXCR3

Abstract: Chemokine receptor CXCR3 has attracted much attention, as it is thought to be associated with a wide range of immunerelated diseases. As such, several small molecules with different chemical structures targeting CXCR3 have been discovered. Despite limited clinical success so far, these compounds serve as interesting tools for investigating receptor activation and antagonism. Accumulating evidence suggests that many of these compounds are allosteric modulators for CXCR3. One feature of allosteric ligands is tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 29 publications
5
23
0
Order By: Relevance
“…Performing chemotaxis assays as previously described, 8 we found that CLL cells pre-stimulated with either CXCR3 ligand CXCL9, CXCL10, or CXCL11 exhibited significantly reduced directed cell migration towards CXCL12 ( Figure 2Ai). Pre-stimulation with a small-molecule high-affinity CXCR3 agonist (VUF11418) 9 confirmed this observation and an antagonist (VUF11211) 9 did not interfere with chemotactic ability (Figure 2Aii).…”
supporting
confidence: 58%
“…Performing chemotaxis assays as previously described, 8 we found that CLL cells pre-stimulated with either CXCR3 ligand CXCL9, CXCL10, or CXCL11 exhibited significantly reduced directed cell migration towards CXCL12 ( Figure 2Ai). Pre-stimulation with a small-molecule high-affinity CXCR3 agonist (VUF11418) 9 confirmed this observation and an antagonist (VUF11211) 9 did not interfere with chemotactic ability (Figure 2Aii).…”
supporting
confidence: 58%
“…G418 was purchased from Duchefa (Haarlem, The Netherlands). 125 I- CXCL10, [ 3 H]-VUF11211 (38.4 Ci/mmol) [ 31 ], and Whatman GF/C filter plates were purchased from Perkin Elmer (Groningen, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…The radioligand binding assay was performed in a similar fashion as described previously by Scholten et al [ 31 ]. Shortly, the [ 3 H]-VUF11211 radioligand was dissolved in binding buffer (50 mM Tris-HCl buffer pH 7.4 at room temperature, 100 mM NaCl, 0.1 % Tween 80, and 0.1 % BSA) and added to wells containing ligand or collected high-resolution fractions of the ligands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that sense, the receptor is the target of ligands that through receptor‐conformational changes aim at blocking different stages in the viral fusion process. One such ligand is maraviroc, the first CCR5 antagonist approved by both the European Medicines Agency and the US Food and Drug Administration (FDA) for treatment of HIV‐infected patients experiencing virological failure due to resistance to other classes of antiretroviral drugs . It represents a novel class of antiretroviral drugs, as it is the first therapeutic targeting a cellular rather than a viral protein.…”
Section: Introductionmentioning
confidence: 99%